2020
DOI: 10.1002/eat.23459
|View full text |Cite
|
Sign up to set email alerts
|

The clash of culture and cuisine: A qualitative exploration of cultural tensions and attitudes toward food and body in Chinese young adult women

Abstract: Objective Accumulating evidence suggests that the prevalence of eating disorders among Chinese women is a public health concern. Prior studies have drawn linkages between conflicting cultural values, identity confusion, and eating disorder symptomatology, which may be relevant for understanding the rise of eating disorders amidst China's rapid economic and sociocultural transformation. Here, we explore how women's experiences with traditional eating norms and modernizing norms of femininity may shape their foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The possible reason may be the rapid advancement, idealism and vast media involvement as many studies suggested that media plays an important key role in the cause of EDs (15). Depiction of personal appearance, pressure, and complained of disordered eating and dissatisfaction of the body are endorsed by media and young ones are more attracted towards this (14,30). ED could be present in both males and females, however, the proportion of males with EDs were smaller than females in many previous studies (7,20).…”
Section: Discussionmentioning
confidence: 99%
“…The possible reason may be the rapid advancement, idealism and vast media involvement as many studies suggested that media plays an important key role in the cause of EDs (15). Depiction of personal appearance, pressure, and complained of disordered eating and dissatisfaction of the body are endorsed by media and young ones are more attracted towards this (14,30). ED could be present in both males and females, however, the proportion of males with EDs were smaller than females in many previous studies (7,20).…”
Section: Discussionmentioning
confidence: 99%
“…In future research, investigators should assess the function of food and norms surrounding food culture for SAs. Similar to Chinese groups (Ng et al, 2021), SA women noted it is considered disrespectful to refuse additional helpings of food, which may encourage overeating, lossof-control eating, and/or binge eating. Furthermore, cultural considerations, including light-skin ideals, marriage pressures, and dual appearance pressures, need to be incorporated into ED assessments to improve identification of ED symptoms in this group.…”
Section: Clinical Implications and Future Directionsmentioning
confidence: 94%
“…A consistent weakness of all the studies was the lack of discussion regarding the authors' cultural and theoretical positioning in the respective study. A small number of studies briefly described the researchers' background (mainly bilingual ability or expertise) [24,26,30,31,34,40], but none discussed the researchers' potential influence on the study. Only five studies used theories or theoretical frameworks to design the research [32,35,42,44,47].…”
Section: Assessment Of Methodological Qualitymentioning
confidence: 99%
“…In family settings, the consideration of other family members was a common factor influencing participants' food choices. For instance, young adult women reported eating unwanted food or overeating to avoid conflict and to show respect and gratefulness to the cook [34]. Chinese immigrants who grew up in China still preferred a Chinese diet after moving overseas [25,28,29,32,35,36,[40][41][42].…”
Section: The Desire To Maintain Harmony In Family/community Influences Food Choicesmentioning
confidence: 99%